Effect of entrepreneurial education and creativity on entrepreneurial intention in college students: mediating entrepreneurial inspiration, mindset, and self-efficiency - Li, Yue; Cao, Keyan; Jenatabadi, Hashem Salarzadeh (Frontiers in Psychology, 2023)
Entrepreneurship in higher education is increasingly valuing entrepreneurial creativity as a significant driver for improving university students' innovative abilities. The purpose of this study was to examine the direct influence of entrepreneurial education and creativity on entrepreneurial intention, as well as the indirect role of entrepreneurial inspiration, mindset, and self-efficiency. This study gathered survey responses from 448 university business students from three Chinese provinces of Shandong, Jiangsu and Zhejiang. The results indicated that entrepreneurial education and creativity have a positive and significant effect on entrepreneurial intent. In addition, the results demonstrated that the combination of entrepreneurial mindset, inspiration, and self-efficacy partially mediates the relationship between entrepreneurial education and entrepreneurial creativity. In addition, additional implications and restrictions are discussed in this article.